Given the equation:
![(x-8a)/(6)=3a-2x](https://img.qammunity.org/2023/formulas/mathematics/college/cv3f53pv74qfn1d27wdmdvxexy9s1jvgo1.png)
To solve for x, first we move the 6 to the other side of the equation:
![\begin{gathered} (x-8a)/(6)=3a-2x \\ \Rightarrow x-8a=(3a-2x)\cdot6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qdkiwa5gho138agvdrxzjt82r8gcihh0xq.png)
Since the 6 was dividing, we pass it to the other side multiplying. Now we apply the distributive property and move the term -8a to the other side:
![\begin{gathered} x-8a=(3a-2x)\cdot6 \\ \Rightarrow x-8a=18a-12x \\ \Rightarrow x=18a-12x+8a \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/xquiz24gzvqr7u50b00gmiqmvkzz8p6kwv.png)
Finally, we move the -12 to the other side with its sign changed:
![\begin{gathered} x+12x=18a+8a=26a \\ \Rightarrow13x=26a \\ \Rightarrow x=(26)/(13)a=2a \\ x=2a \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/9aktm83k48g530oclieas01pxx280mlkup.png)
therefore, x=2a